Comparative Usability Analysis of Selected Data Entry Methods for Web Systems. Issue 2 (17th February 2020) - Osada, Krzysztof; Muke, Patient Zihisire; Piwowarczyk, Mateusz; Telec, Zbigniew; Trawiński, Bogdan
Abstract: This paper addresses usability problems of data entry techniques and patterns in web systems and web sites. In order to carry out a comparative analysis of the solutions a dedicated web application was developed as an experimental tool for performing usability testing. The application was designed in the form of a test divided into scenarios and exercises on filling up selected models. Furthermore, the application recorded usability metrics, questionnaires, open and closed questions, as well as users' personal data. 40 participants, who took part remotely in the experiment, were split into two distinct groups and completed two separate tests that differed in input data and tested solutions. Some measures referring to the effectiveness, efficiency, and user satisfaction were collected. The results were thoroughly analyzed and the recommendations for the usage of particular models were formulated.